Mrs. Frisby and the rats of Nimh - O'Brien, Robert C.; Bernstein, Zena (New York, NY : Atheneum Books for Young Readers, 1971)
Having no one to help her with her problems, a widowed mouse visits the rats whose former imprisonment in a laboratory made them wise and long lived
790
Newbery Medal, 1972
Keywords: Mice -- Juvenile fiction; Rats -- Juvneile fiction; Newbery Medal